Engagement Policies in Favour of Transnationalism: the expansion of transnational citizenship within Colombian emigrants - González-Rábago, Yolanda (2015)
Communities of nationals living abroad are attracting the interest of sending countries, which are paying increasing attention to the way in which emigrants connect with their origin and the potential benefits of it. Focusing on the case of Colombia and analysing the initiatives under the Colombia Nos Une Program, this article examines the role that the proactive attitude of institutional actors is playing in the potential engagement of migrants with their country of origin and the creation of a transnational citizenship. Colombia, as a sending country, is looking at their emigrants in an attempt to take advantage of their economic and human capital in order to improve its development through networks of knowledge, entrepreneurship and socio-cultural initiative. An increasing knowledge of the way policies of origin are implemented and the impact they have on the migrants’ lives will give a more comprehensive framework to understand the effects of a transnational life and to conceptualize a transnational citizenship. Comunidades de emigrantes que moram no exterior têm atraído o interesse dos países emissores, que têm prestado mais atenção a como os emigrantes interagem com seus países de origem e aos potenciais benefícios dessa interação. Ao focar no caso da Colômbia e ao analisar as iniciativas do programa Colombia Nos Une, este artigo examina o papel que a proatividade de atores institucionais tem no engajamento potencial de migrantes com seus países de origem e na criação de uma cidadania transnacional. A Colômbia, como país emissor, tem buscado aproveitar o capital econômico e humano dos seus emigrantes para aprimorar o seu desenvolvimento, por meio de redes de conhecimento, empreendedorismo e iniciativa sociocultural. Um maior conhecimento de como as políticas de origem são implementadas e do impacto que elas têm nas vidas dos migrantes dará uma visão mais abrangente, para entender os efeitos de uma vida transnacional e conceituar a cidadania transnacional.